Determination of the early Paleozoic accretionary complex in Southwestern Yunnan, China: Implications for the tectonic evolution of the Proto-Tethys Ocean - Guo-chuan Yan; Bao-di Wang; Han Liu; Juan He; Zhi-min Peng (China Geology)
ABSTRACT: Accretionary complex study provides important knowledge on the subduction and the geodynamic processes of the oceanic plate, which represents the ancient ocean basin extinction location. Nevertheless, there exist many disputes on the age, material source, and tectonic attribute of the Lancang Group, located in Southwest Yunnan, China. In this paper, the LA-ICP-MS detrital zircon U–Pb chronology of nine metamorphic rocks in the Lancang Group was carried out. The U–Pb ages of the three detrital zircons mainly range from 590–550 Ma, 980–910 Ma, and 1150–1490 Ma, with the youngest detrital zircons having a peak age of about 560 Ma. The U–Pb ages of the six detrital zircons mainly range from 440–460 Ma and 980–910 Ma, and the youngest detrital zircon has a peak age of about 445 Ma. In the Lancang Group, metamorphic acidic volcanic rocks, basic volcanic rocks, intermediate-acid intrusive rocks, and high-pressure metamorphic rocks are exposed in the form of tectonic lens in schist, rendering typical melange structural characteristics of “block + matrix”. Considering regional deformation and chronology, material composition characteristics, and the previous data, this study thinks the Lancang Group may be an early Paleozoic tectonic accretionary complex formed by the eastward subduction of the Changning-Menglian Proto-Tethys Ocean, which provides an important constraint for the Tethys evolution.©2023 China Geology Editorial Office.